Factors that facilitate the consumption of psychoactive substances in adolescents - Egocheaga Contreras, Marth (2003)
In many countries, the use of psychoactive substances in child and adolescents is reported very young ages. Additionally, an evident concern is the evolution of the type of substances which is used in our environment; although their use is not massive, the risk is latent. The author poses a reflection on the main factors causing the use of psychoactive substances in adolescent.